SERI FANTASTEEN GHOST DORMITORY: PRODUKSI KOMERSIAL SASTRA DI INDONESIA - Adji, Alberta Natasia (Universitas Negeri Surabaya, 2016)
The trend of horror genre has spread towards Indonesian literature, marked by the emergence of light noves for teenagers aged 13-18 under the label of Fantasteen, an imprint of DAR! Mizan starting in 2011, a division of PT Mizan Pustaka, one of the biggest publishing companies in Indonesia. Among various printed Fantasteen light novels, the Ghost Dormitory series became the most prominent work as each story is set in one foreign city such as Tanzania, Den Haag, etc. The study reveals the interconnecting phenomenon between literary works and commercial ways through the perspective of Pierre Bourdieu?s the field of cultural production and Tzvetan Todorov?s Fantastic theory. Using a qualitative method, this article proves that DAR! Mizan has successfully achieved popular legitimation owing to the rising horror-themed light novels which are presented through Fantasteen brand, written by teenagers and also targeted for young readers. With the rise of the special series Ghost Dormitory among other Fantasteen works, the result of the study shows that as one of the major publishers, DAR! Mizan has successfully conducted a strategy to influnce the face of the Indonesian teenage literary world which is presenting a horror genre as its main theme.